Ivanovo City Agglomeration: Mini-Portraits оf Settlements (based on the materials of the expedition) - V. V. Chikhichin; I. A. Soloviev; J. F. Zolnikova; E. I. Ovsyannikov (Наука. Инновации. Технологии, 2022)
Introduction. In October 2021, a team of authors made an expedition to the Ivanovo region in order to study the demographic development of the urban agglomeration, the core of which is the center of this region. On the basis of travel observations, general geographical, with an emphasis on socio-economic processes, mini-portraits of the cities of Ivanovo, Kokhma, Shuya, Vichuga, Teikovo, Gavrilov Posad, Plyosa, and the town. Palekh and Kineshma, which is not part of the agglomeration.Materials and methods. The key research method is visual observation and a survey of the local population. The work also used official statistics on the population of settlements.Results and discussion. The article gives mini-portraits of settlements in accordance with the classical scheme of the economic and geographical characteristics of the territory, namely, it describes: economic and geographical position, natural conditions, history of formation, population, economy, improvement.Conclusions. The strength of the interaction of settlements within the Ivanovo urban agglomeration is not as great as in many other agglomerations of our country. And the reason for this is the proximity of Moscow, which in many ways pulls over the functions of the core. The image of the depressive territory during the expedition was not justified to a large extent. Cities are alive and trying to develop. Some do it better, others worse.